Calculati : (-rad. din 2) la a 3 x (-rad din 2 ) =
Răspunsuri la întrebare
Răspuns de
0
[tex](-\sqrt2)^3\;\cdot\;(-\sqrt2)=\underbrace{(-\sqrt2)\cdot(-\sqrt2)\cdot(-\sqrt2)}\cdot(-\sqrt2)=\\
.\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=(-\sqrt2)^{3+1}=+\sqrt{2^4}=4[/tex]
alitta:
Cu placere !
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă